Developing a Community-Based Smart Edu-Tourism Model: Integrating Green Marketing and Artificial Intelligence for Urban Sustainability - Amelia Naim Indrajaya; Yulita Fairina Susanti; Eka Sri Dana Afriza; Hamid H. Kazeroony (Sekolah Tinggi Manajemen IPMI, 2026)
Community-based edu-tourism in urban areas is a promising approach to sustainability, cultural preservation, and community empowerment, but many initiatives struggle with competitiveness and digital adaptation after the pandemic. While green marketing provides an ecological framework and smart tourism highlights the potential of AI and digital tools, their integration remains limited, particularly in urban edu-tourism. This paper proposes a conceptual framework combining the seven dimensions of green marketing with AI-enabled smart tourism to create smart, sustainable, and personalized edu-tourism experiences. The study contributes theoretically by extending sustainability marketing through technological enablers, and practically by offering guidance for policymakers, tourism managers, and communities to design competitive edu-tourism models aligned with the United Nations Sustainable Development Goals (SDGs).